Efficient Two-Step Multifunctionalization of Substituted 2-Hydroxyglycopyranosides - Franconetti, Antonio; Álvarez, Eleuterio; Cabrera-Escribano, Francisca (Synlett, 2017)
A straightforward route to diversely functionalized glycopyranosides is reported. 2,3-Enopyranosides, 2- and/or 3-azido-, 2-halopyranosides, and a hex-3-ulose, among other α- and β-glycopyranosides are easily obtained in good to excellent yields from 2-hydroxyglycopyranosides by means of a two-step process involving trifluoromethanesulfonation and subsequent treatment with the appropriate nucleophilic agent.
Keywords: functionalized glycopyranosides; 2-hydroxyglycopyranosides; 2,3-enopyranosides; 2-halopyranosides; DFT calculations; conformational analysis